Філософський вимір духовних цінностей - Тронько, О. О. (ХНУРЕ, 2021)
The article considers the moral aspects of philosophical activity. It is argued that the difference between philosophical thinking and moral thinking is inherent in the moral thinking of every person, regardless of its group, national, religious affiliation. Moral consciousness is formed for each individual during life on the basis of everyday life experience. Formed moral principles man regulates his behavior due to the fact that he is a human being. However, ethical concepts and ideas, while maintaining its normatively binding value, are the basis of the moral world.
Keywords: філософія; духовні цінності